The Immediate Effect of Crude Miswack Extract against Some Bacterial isolates from Gingivitis - Ali Muhammid, Hayder; Naji Ayyez, Hayder; Muhammed Khudaier, Amaal; M. Khalaf, Jassim (Al-Qadisiyah Journal of Pure Science, 2018)
This study included the isolation and identification of some bacterial species which are considered as members of gingivitis in the student of Veterinary Medicine College in the University of Kerbala, Iraq . These include the of Streptococcus spp. was more involved in the third stage 70% percentage and Staphylococcus spp. was more isolated in the second stage 40% percentage by using Blood Agar medium and Manitol Salt agar, respectively. Identification of these bacteria was erformed depending on morphological and biochemical crieteria, the study includes also the effect of the aqueous extract of Salvadora persica in the concentrations (20%, 15% and 10%) on the isolated bacteria which showed antimicrobial effects on these species under the study. Biology Classification: QR75-99.5